Kecepatan Aliran Air Tanah Pada Sumur Pantau Menggunakan Paper Disc Velocimeter - Roza Wahyuni; Rinaldi Rinaldi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Paper disc velocimeter is a device used as a gauge groundwater flow movement which includes the velocity and direction of water flow in media. Paper disc velocimeter is a measurement of groundwater flow originating from Japan, therefore for use in Indonesia there are several obstacles such as the type of paper and ink used that are not available in Indonesia, therefore replacing paper and local ink is easily obtained. The aim of this research is to test a large number of local papers in Pekanbaru to be applied to groundwater flow measuring devices using local papers materials, replacement is carried out by replacing paper types with paper in Pekanbaru, paper used totaling 3 types of paper characteristics, testing is done by conducting measurement using a velocimeter paper disc inserted into the monitoring well with a predetermined time. The test results are the equation used to find the groundwater flow velocity on the paper disc. Paper one has the characteristics of fine fibers, having velocity ranging ffrom 0 to 0,341 cm/minute.Keyword: Paper disc velocimeter, groundwater, material local